2016
DOI: 10.1002/cbic.201600023
|View full text |Cite
|
Sign up to set email alerts
|

ASGPR‐Mediated Uptake of Multivalent Glycoconjugates for Drug Delivery in Hepatocytes

Abstract: Liver cells are an essential target for drug delivery in many diseases. The hepatocytes express the asialoglycoprotein receptor (ASGPR), which promotes specific uptake by means of N-acetylgalactosamine (GalNAc) recognition. In this work, we designed two different chemical architectures to treat Wilson's disease by intracellular copper chelation. Two glycoconjugates functionalized with three or four GalNAc units each were shown to enter hepatic cells and chelate copper. Here, we studied two series of compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Because BzlSer is a competitive inhibitor for ASCT2 with an inhibition constant ( K i ) of 0.9 mM 29 , apparent K d values of these polymers can be estimated by assuming a simple inhibition model 30 . PLys(Gln)-100 showed apparent K d value of 62 nM, which is comparable to the K d value of potent ligands 13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BzlSer is a competitive inhibitor for ASCT2 with an inhibition constant ( K i ) of 0.9 mM 29 , apparent K d values of these polymers can be estimated by assuming a simple inhibition model 30 . PLys(Gln)-100 showed apparent K d value of 62 nM, which is comparable to the K d value of potent ligands 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The cells were analysed using flow cytometer, and half maximal inhibitory concentrations (IC 50 ) of BzlSer were calculated. Apparent dissociation constant ( K d ) of the polymers were estimated using the obtained IC 50 values, following Cheng-Prusoff equation (1) 30, 39 :where K i is the apparent inhibition constant of BzlSer for ASCT2 (0.9 mM), and [L] is the polymer concentration in this assay. For the inhibition of PLys(Gln)-50 and PLys(α-Glu)-100, concentration of both polymers was changed to 3 μM.…”
Section: Methodsmentioning
confidence: 99%
“…With these aldehyde surfaces in hand, four aminooxyglycosylated structures have been synthesized to be immobilized. On the basis of recent binding studies performed with lectin and cyclopeptide-based glycoclusters in solution [30][31][32][33][34][35][36][37] and on solid-support, [38][39][40][41] we have selected similar structures ( Fig. 2) for this study that are: (i) tetravalent cyclopeptides displaying β-lactose 1a or α-N-acetylgalactosamine 1b and (ii) monomeric glycans 2a-b 40 which are selective for lectins PNA from Arachis hypogaea ( peanut) and HPA (Helix pomatia agglutinin) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests the sharp difference in preferred multivalent glycostructures of ASGPr and MR probably because of the different membrane-bound architectures of the receptors. [26][27][28] To corroborate the receptor-targeting ability of the probes, a competition assay was carried out. The result indicated that the presence of increasing free D-mannose and D-galactose gradually suppressed the fluorescence of poly-CD 100 and poly-CD 6 probe produced in MDA-MB-231 and Hep-G2 cells, respectively (Fig.…”
Section: Figmentioning
confidence: 99%